ETIOLOGICAL ASPECTS OF EPISTAXIS AND ALTERNATIVE WAYS TO STOP IT - B.N. SHAMSIDINOV; P.R. MUKHTOROVA; T.KH. OLIMOV; Z.A. AKHROROVA (Avicenna Tajik State Medical University, 2020)
Objective: To study the etiology of epistaxis and to improve the mechanical ways to stop it. Methods: 354 patients with nose bleeding aged 6 months to 78 years were examined from 2,360 people who applied to the urgent ENT Department of the National Medical Center of the Republic Tajikistan, which was 15%. They conducted an otorhinolaryngological examination, evaluation of the general state, finding out the causes of nasal bleeding and all necessary measures to stop it. Results: Out of 354 patients, 339 (95.6%) provided the first emergency care in the urgent ENT Outpatient Department, and 15 (4.2%) hospitalized in ENT Department. Among general and local causes, cardiovascular disease, respiratory infections, chronic atrophic and subatrophic processes of nose mucous were identified. In 297 (83.4%) had a combination of those and other causes. The majority of patients (n=209; 58.5%) suffered from cardiovascular pathology, in particular hypertension and atherosclerosis, in 19 (5.5%) patients the nasal bleeding occurred during the period or after recently suffered acute respiratory infections. Only in 51 (14.4%) patients identified local causes of nasal bleeding, of which 15 patients were hospitalized in the ENT Department. Bleeding was stopped by the anterior nasal tamponade in 6 cases, the anterior and posterior tamponade - in 8 observations, and in one patient, with inefficiency of the posterior and anterior tamponade, ligation of external carotid artery was performed. An alternative method has been used as a rear tamponade for the first time using a device made from a conventional endotracheal tube with an inflatable cuff on the distal end. The method has proven to be more gentle and less traumatic, allowing keeping nasal breathing through the tube. This provides the best quality of postoperative management, and at times accelerates the rehabilitation process. Conclusion: The results show that the causes of nasal bleeding are most often caused by general somatic pathology and only in 14.4% of cases are associated with pathology of nasal cavity. The proposed alternative method of posterior tamponade has shown good results and the possibility of its wide practical application, especially in terms of first aid.